2018
DOI: 10.3389/fpsyt.2018.00311
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Life Memories Relate to Ruminative Thoughts in Women With Sexual Violence History, Irrespective of PTSD

Abstract: More than one in every four women in the world experience sexual violence (SV) in their lifetime, most often as teenagers and young adults. These traumatic experiences leave memories in the brain, which are difficult if not impossible to forget. We asked whether women with SV history experience stronger memories of their most stressful life event than women without SV history and if so, whether strength relates to ruminative and trauma-related thoughts. Using the Autobiographical Memory Questionnaire (AMQ), wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 93 publications
(101 reference statements)
1
8
0
Order By: Relevance
“…Rumination (self-punishment) was positively associated with depression, generalized anxiety, PTSD and CG symptomatology consistent with our hypotheses and the prior literature (Dar, 2015;Eisma et al, 2014;2015a;2015b;2017;Papargeorgiou & Wells, 2003;. Ruminations are generally can strengthen the loss narrative because the memory is repeatedly re-consolidated (Millon et al, 2018). A stressful event may also alter an individual's locus of control and belief in a just world (Nowicki et al, 2019;Stroebe, 2015) thus contributing to intrusive or deliberate rumination, as a way of coping.…”
Section: )supporting
confidence: 89%
See 1 more Smart Citation
“…Rumination (self-punishment) was positively associated with depression, generalized anxiety, PTSD and CG symptomatology consistent with our hypotheses and the prior literature (Dar, 2015;Eisma et al, 2014;2015a;2015b;2017;Papargeorgiou & Wells, 2003;. Ruminations are generally can strengthen the loss narrative because the memory is repeatedly re-consolidated (Millon et al, 2018). A stressful event may also alter an individual's locus of control and belief in a just world (Nowicki et al, 2019;Stroebe, 2015) thus contributing to intrusive or deliberate rumination, as a way of coping.…”
Section: )supporting
confidence: 89%
“…Some individuals are generally prone to engage in rumination, which appears to underlie several psychological disorders. While past research conceptualized rumination as a relatively stable trait, newer evidence suggests that effective intervention can target rumination (Millon et al, 2018).…”
Section: )mentioning
confidence: 99%
“…Recently, Millon and colleagues (2018) found that women who experienced sexual violence in adolescence, but who did not develop PTSD, reported particularly strong memories for stressful life events in adulthood. In these women, intrusive memories of autobiographical stressful events correlated with the presence of altered cognitions related to traumatic life experiences and with an increased level of anxiety and depression [ 64 ].…”
Section: Intentional and Incidental Forgetting In Post-traumatic Stress Disordermentioning
confidence: 99%
“…Clinical and community studies indicate that the program, when practiced over weeks, can increase aspects of mental health, especially reducing symptoms of depression and the occurrence of ruminative thoughts. For example, women with sexual violence history who engaged in 6 weeks of MAP Training reported fewer numbers of ruminative and trauma-related cognitions, as well as greater self-worth (Millon et al, 2018 ; Shors & Millon, 2016 ; Shors et al, 2018 ). In another study, women with substance dependence were less anxious and acquired greater cardiovascular fitness (measured as VO 2 ) (Shors et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%